Method for respectively preparing battery-grade nickel sulfate and ferrous sulfate by taking ferro-nickel alloy as raw material
By pressurizing the method of oxidation and immersion and resin column adsorption, the problem of low immersion rate and low separation efficiency during the nickel and iron alloy wetting method of nickel iron alloy is solved, and the efficient separation and leaching of nickel and iron are realized.
Patent Information
- Application Number
- CN202411514416.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems of high crushing cost and low leaching rate in the wet leaching process of nickel-ferroalloys, and it is difficult to effectively separate nickel and iron.
The nickel -iron alloy is immersed in the acid solution in a compressed oxidation immersion method, the proportion of oxygen is controlled to obtain a binary iron, and the nickel and iron are separated through the adsorption process of the resin column.
The immersion rate of nickel and iron is improved, the efficient separation of nickel iron is achieved, the production of hydrogen during the immersion process is reduced, and the degeneration and adsorption performance of the resin can be avoided.
Smart Images

Figure CN119330416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of regeneration application of nickel-iron alloys, and in particular relates to a method for preparing battery-grade nickel sulfate and ferrous sulfate respectively by taking the nickel-iron alloy as a raw material. Background Art
[0002] As an energy storage solution, batteries play an important role in the green transition to carbon neutrality. As an important precursor material for nickel cobalt manganese oxide batteries, the market for nickel sulfate will continue to expand as battery energy density increases and costs decrease.
[0003] As an important inorganic chemical raw material, ferrous sulfate increases the solubility of batteries while maintaining the stability of battery electrolytes. Therefore, it is widely used in the production of various batteries, such as lead-acid and manganese-acid batteries, and its market prospects are bright.
[0004] China's nickel ore resources are relatively scarce, accounting for only 2.1% of the world's total. However, nickel-iron alloy is not only abundant in supply but also relatively cheap, making it an important raw material for the preparation of battery-grade nickel sulfate and ferrous sulfate. With the increasing demand for environmental protection, hydrometallurgical technology has been widely used in the field of metal recovery. However, in the process of wet leaching of nickel-iron alloy and stainless steel, it is often accompanied by problems such as crushing cost and low leaching rate. And it is still a key issue for the subsequent improvement of the separation efficiency of nickel and iron.
[0005] Based on this, a new method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials is proposed, so as to achieve nickel-iron separation while improving the separation effects of nickel and iron respectively. Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw material, which method not only improves the leaching rate of iron and nickel in the nickel-iron alloy, but also can effectively separate iron and nickel at the same time, thereby improving the separation effect of the two.
[0007] Technical solution: The method of the present invention uses nickel-iron alloy as raw material to prepare battery-grade nickel sulfate and ferrous sulfate respectively, comprising the following steps:
[0008] (1) immersing the nickel-iron alloy in an acid solution and leaching under pressure at a volume ratio of N2 to O2 of (7-9):(1-3) to obtain a leachate S1;
[0009] (2) adding a neutralizing agent to the leachate S1 to adjust the pH to 2.5-3, precipitating chromium and performing solid-liquid separation to obtain a solution S2;
[0010] (3) adding a reducing agent to solution S2 to obtain solution S3;
[0011] (4) passing the solution S3 through a resin column having an H-type and Na-type molar ratio of 1:(0.5-4) to separate the nickel ions alone and simultaneously obtain a solution S4 containing ferrous sulfate after adsorption, and separating the solution S4 to obtain ferrous sulfate;
[0012] (5) Desorbing the resin to obtain a nickel sulfate solution, and then evaporating, concentrating, cooling and crystallizing to obtain nickel sulfate crystals.
[0013] The invention is based on the use of pressurized oxidation leaching to fully utilize the nickel-iron alloy without crushing it, and obtain ferrous ions, which are beneficial for the subsequent separation of nickel and cobalt by resin. While improving the leaching rate of iron and nickel, the generation of hydrogen during the leaching process can be prevented.
[0014] The present invention is based on the iron and nickel leaching, on the one hand, by controlling the ratio of oxygen, directly obtaining ferrous iron, reducing the adsorption of ferric iron ions by the active sites occupied on the resin (i.e., the active sites occupied by ferrous iron on the resin are less than ferric iron), promoting the adsorption of nickel by the resin, and realizing the efficient separation of nickel and iron, on the other hand, before the resin adsorption is adopted, a reducing agent is first introduced, and then the stability in the resin adsorption process can be effectively promoted, reducing the oxidation of the carbon chain or functional group of the resin by the adsorbed liquid containing many oxidizing substances to cause the carbon chain fracture and the change of the functional group, effectively avoiding the denaturation of the resin, and reducing the adsorption performance. And by regulating the ratio of H type and Na type in the resin, on the one hand, the acid and alkali dosage can be reduced, and the pH increase after the liquid flows through the resin column can also be prevented to generate precipitation of some cations therein, blocking the resin, and further improving the adsorption performance of the resin.
[0015] Furthermore, in step (1) of the method of the present invention, the leaching temperature is 100-200° C., the oxidation leaching time is 6-10 h, and the solid-liquid ratio of the nickel-iron alloy to the acid solution is 1:(1-40) g / L.
[0016] Furthermore, in step (1) of the method of the present invention, the leaching rate of nickel in the leaching solution S1 is 98-100%, the leaching rate of iron is 95-100%, and the leaching rate of chromium is 60-80%.
[0017] Furthermore, in step (2) of the method of the present invention, the neutralizing agent is iron powder or nickel hydroxide.
[0018] Furthermore, in step (3) of the method of the present invention, the reducing agent includes sodium disulfite, sodium sulfite or sodium bisulfite.
[0019] Furthermore, in step (4) of the method of the present invention, the resin column with a molar ratio of H-type to Na-type of 1:(0.5-4) is obtained by the following steps: determining the amount of sulfuric acid required for the full capacity when the Na-type is converted into the H-type resin, and then acid washing the Na-type resin according to the amount of acid added when the conversion to the H-type to Na-type molar ratio of 1:(0.5-4) = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0020] Furthermore, in step (4) of the method of the present invention, the adsorption flow rate is about 0.4-1 BV / h.
[0021] Furthermore, in step (5) of the method of the present invention, the desorbent used for desorption is a 20-40% sulfuric acid solution, the volume of the sulfuric acid solution is 3-5BV, the desorption rate is 1-4BV / h, and the desorption rate can reach 96-99%.
[0022] Furthermore, in step (5) of the method of the present invention, the evaporation and concentration temperature is 60-100°C, and the nickel concentration in the liquid after evaporation and concentration is 60-100 g / L; and the cooling crystallization temperature is 0-20°C.
[0023] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials can make the nickel leaching rate in the nickel-iron alloy reach 98-100%, the iron leaching rate reach 95-100%, and the chromium leaching rate reach 60-80%, effectively improving the leaching rate of nickel and iron; and the method can achieve an adsorption rate of nickel of 98-100%, realizing the full separation of nickel and iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Flow chart of the method of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0026] It should be noted that the calculation formula of the leaching rate of the present invention is: leaching rate = mass of metal in liquid / mass of metal in nickel-iron alloy.
[0027] The calculation formula of the leaching rate is: adsorption rate = (nickel content of the sample solution - nickel content of the solution after adsorption) / nickel content of the sample solution.
[0028] The calculation formula of desorption rate is: desorption rate = nickel content of liquid after desorption / (nickel content of sample liquid - nickel content of liquid after adsorption).
[0029] The resin column with a molar ratio of H type to Na type of the present invention of 1: (0.5-4) is obtained by the following steps: determining the amount of sulfuric acid required for the full capacity when the Na type is converted into the H type resin, and then acid washing the Na type resin according to the amount of acid added when the H type and Na type molar ratio is 1: (0.5-4) = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type. Specifically, the Na type resin is washed with an acid solution with a concentration of 4-10%, and washed to neutrality when the pH reaches 3-4; 5 mL of the resin is soaked in 200 mL of 1 mol / L sodium hydroxide solution for 2 hours, 20 mL of the soaking solution is taken, phenolphthalein is added thereto, and 1 mol / L sulfuric acid is used to titrate until the red color is basically faded to obtain the resin converted into the H type and the amount of sulfuric acid required for the full capacity, and then acid washing the Na type resin according to the amount of acid added when the H type and Na type molar ratio is 1: (0.5-4) = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0030] Example 1
[0031] like Figure 1 As shown, the method of preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials in this embodiment comprises the following steps:
[0032] (1) Weigh 50 g of nickel-iron alloy (main content: Ni: 20.5%; Fe: 64.8%; Cr: 4.2%), mix it with a 20% mass fraction sulfuric acid solution in a pressure autoclave at a solid-liquid ratio of 1:10, react for 7 hours under the conditions of a N2:O2 volume ratio of 9:1 and a leaching temperature of 120°C, and then filter to obtain a leachate S1. The leaching rates of nickel, iron and chromium in the leachate S1 are calculated to be 98.6%, 97.2% and 76.5% respectively. Potassium thiocyanate is used to detect trivalent iron ions in the leachate, and it is found that potassium thiocyanate does not change color, thereby verifying that the pressurized oxidative leaching directly obtains divalent iron in the leachate by controlling the oxygen ratio.
[0033] (2) Iron powder is slowly added to the leaching solution S1, during which the pH of the solution is continuously measured. When the pH of the solution is 3.0, the addition is stopped and the solution is filtered to obtain a chromium-free solution S2.
[0034] (3) Sodium bisulfite is added to solution S2 to protect the resin and prevent oxidation of divalent iron.
[0035] (4) Wash the Na-type resin with a 4% acid solution until the pH reaches 3-4 and the resin is washed to neutral; soak 5 mL of the resin in 200 mL of a 1 mol / L sodium hydroxide solution for 2 h, take 20 mL of the soaking solution, add phenolphthalein thereto, and titrate with 1 mol / L sulfuric acid until the red color is basically faded to obtain the H-type resin and the amount of sulfuric acid required for the full capacity, and then acid wash the Na-type resin according to the amount of acid added when the molar ratio of the H-type to the Na-type is 1:2 = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0036] (5) The solution S3 is passed into a CH-90 resin column with a mass ratio of H type to Na type of 1:2, and its flow rate is controlled to be 0.5 BV / h. Nickel is adsorbed by the resin, and the adsorption rate of nickel reaches 99.3%. The adsorbed solution S4 is obtained, that is, a solution containing ferrous sulfate. Ferrous sulfate can be obtained by further separation, that is, evaporation concentration or cooling crystallization.
[0037] (6) A sulfuric acid solution with a mass fraction of 40% was used to desorb the resin. The volume of sulfuric acid was 3BV and the desorption rate was 2BV / h. Then, 2BV of pure water was used for washing. The desorption liquid mixed with the sulfuric acid desorption liquid was used to measure the nickel content. The nickel desorption rate was 99.2%.
[0038] (7) The nickel sulfate solution obtained in step (6) was evaporated and concentrated at 80° C. for 6 h, and the concentration of nickel sulfate in the concentrated solution was 90 g / L.
[0039] (8) The concentrated liquid was cooled and crystallized at 10°C for 4 hours to obtain nickel sulfate crystals.
[0040] Example 2
[0041] The method of preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials in this embodiment comprises the following steps:
[0042] (1) Weigh 50 g of nickel-iron alloy (main content: Ni: 27.1%; Fe: 54.8%; Cr: 6.3%), mix it with a 30% mass fraction sulfuric acid solution in a pressure autoclave at a solid-liquid ratio of 1:20, react for 6 hours under the conditions of N2:O2 volume ratio of 4:1 and leaching temperature of 150°C, and then filter to obtain a leachate S1, in which the leaching rate of nickel, the leaching rate of iron, and the leaching rate of chromium are 99.2%, 98.9%, and 73.2%; and use potassium thiocyanate to detect trivalent iron ions in the leachate, and it is found that potassium thiocyanate does not change color, thereby verifying that the pressurized oxidative leaching controls the oxygen ratio to directly obtain divalent iron in the leachate.
[0043] (2) Slowly adding nickel hydroxide to the leaching solution S1, during which the pH of the solution is continuously measured. When the pH of the solution is 2.5, the addition is stopped and the solution is filtered to obtain a chromium-free solution S2.
[0044] (3) Sodium bisulfite is added to solution S2 to protect the resin and prevent the oxidation of divalent iron.
[0045] (4) Wash the Na-type resin with a 6% acid solution until the pH reaches 3-4 and the resin is washed to neutral; soak 5 mL of the resin in 200 mL of a 1 mol / L sodium hydroxide solution for 2 h, take 20 mL of the soaking solution, add phenolphthalein thereto, and titrate with 1 mol / L sulfuric acid until the red color is basically faded to obtain the H-type resin and the amount of sulfuric acid required for the full capacity, and then acid wash the Na-type resin according to the amount of acid added when the molar ratio of the H-type to the Na-type is 1:1 = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0046] (5) the solution S3 is passed into an iminodiacetic acid chelating resin column having a mass ratio of H type to Na type of 1:1, and the flow rate is controlled to be 0.6 BV / h. The nickel is adsorbed by the resin, and the adsorption rate of the nickel reaches 99.6%. The adsorbed solution S4 is obtained, i.e., a solution containing ferrous sulfate. The ferrous sulfate can be obtained by further separation, i.e., evaporation concentration or cooling crystallization.
[0047] (6) A sulfuric acid solution with a mass fraction of 30% was used to desorb the resin. The volume of sulfuric acid was 3BV and the desorption rate was 2BV / h. Then, 2BV of pure water was used for washing. The desorption liquid mixed with the sulfuric acid desorption liquid was used to measure the nickel content. The nickel desorption rate was 99.1%.
[0048] (7) The nickel sulfate solution obtained in step (6) was evaporated and concentrated at 100° C. for 4 h, and the concentration of nickel sulfate in the concentrated solution was 97 g / L.
[0049] (8) The concentrated liquid was cooled and crystallized at 0°C for 4 hours to obtain nickel sulfate crystals.
[0050] Example 3
[0051] The method of preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials in this embodiment comprises the following steps:
[0052] (1) Weigh 50 g of nickel-iron alloy (main content: Ni: 25.4%; Fe: 68.9%; Cr: 5.3%), mix it with a 30% mass fraction sulfuric acid solution in a pressure autoclave at a solid-liquid ratio of 1:1, react for 10 hours under the conditions of N2:O2 volume ratio of 4:1 and leaching temperature of 100°C, and then filter to obtain a leachate S1, in which the leaching rate of nickel is 98.9%, the leaching rate of iron is 97.2%, and the leaching rate of chromium is 75.6%. The leaching solution is tested for trivalent iron ions using potassium thiocyanate, and it is found that potassium thiocyanate does not change color, thereby verifying that the pressurized oxidative leaching directly obtains divalent iron in the leachate by controlling the oxygen ratio.
[0053] (2) Slowly adding nickel hydroxide to the leaching solution S1, during which the pH of the solution is continuously measured. When the pH of the solution is 2.8, the addition is stopped and the solution is filtered to obtain a chromium-free solution S2.
[0054] (3) Sodium bisulfite is added to solution S2 to protect the resin and prevent oxidation of divalent iron.
[0055] (4) Wash the Na-type resin with an acid solution having a concentration of 8%, and wash it to neutrality when the pH reaches 3-4; soak 5 mL of the resin in 200 mL of a 1 mol / L sodium hydroxide solution for 2 h, take 20 mL of the soaking solution, add phenolphthalein thereto, and titrate with 1 mol / L sulfuric acid until the red color is basically faded to obtain the H-type resin and the amount of sulfuric acid required for full capacity, and then acid wash the Na-type resin according to the amount of acid added when the molar ratio of H-type to Na-type is 1:0.5 = the amount of sulfuric acid required for full capacity / the proportion of hydrogen type.
[0056] (5) the solution S3 is passed into an iminodiacetic acid chelating resin column in which the mass ratio of H type to Na type is 1:0.5, and the flow rate is controlled to be 0.4 BV / h. The nickel is adsorbed by the resin, and the adsorption rate of the nickel reaches 98.3%. The adsorbed solution S4 is obtained, i.e., a solution containing ferrous sulfate. The ferrous sulfate can be obtained by further separation, i.e., evaporation concentration or cooling crystallization.
[0057] (6) A sulfuric acid solution with a mass fraction of 20% was used to desorb the resin. The volume of sulfuric acid was 4BV and the desorption rate was 1BV / h. Then, 2BV of pure water was used for washing. The desorption liquid mixed with the sulfuric acid desorption liquid was used to measure the nickel content. The nickel desorption rate was 98.6%.
[0058] (7) The nickel sulfate solution obtained in step (6) was evaporated and concentrated at 80° C. for 4 h, and the concentration of nickel sulfate in the concentrated solution was 98 g / L.
[0059] (8) The concentrated liquid was cooled and crystallized at 5°C for 4 hours to obtain nickel sulfate crystals.
[0060] Example 4
[0061] The method of preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials in this embodiment comprises the following steps:
[0062] (1) Weigh 50 g of nickel-iron alloy (main content: Ni: 26.8%; Fe: 65.8%; Cr: 7.4%), mix it with a 30% mass fraction sulfuric acid solution in a pressure autoclave at a solid-liquid ratio of 1:40, react for 5 hours under the conditions of N2:O2 volume ratio of 7:3 and leaching temperature of 200°C, and then filter to obtain a leachate S1, in which the leaching rate of nickel, iron and chromium is 98.3%, 98.6% and 79.1% respectively; and use potassium thiocyanate to detect trivalent iron ions in the leachate, and it is found that potassium thiocyanate does not change color, thereby verifying that the pressurized oxidative leaching directly obtains divalent iron in the leachate by controlling the oxygen ratio.
[0063] (2) Slowly adding nickel hydroxide to the leaching solution S1, during which the pH of the solution is continuously measured. When the pH of the solution is 3, the addition is stopped and the solution is filtered to obtain a chromium-free solution S2.
[0064] (3) Sodium sulfite is added to solution S2 to protect the resin and prevent oxidation of divalent iron.
[0065] (4) Wash the Na-type resin with a 10% acid solution until the pH reaches 3-4 and the resin is washed to neutral; soak 5 mL of the resin in 200 mL of a 1 mol / L sodium hydroxide solution for 2 h, take 20 mL of the soaking solution, add phenolphthalein thereto, and titrate with 1 mol / L sulfuric acid until the red color is basically faded to obtain the H-type resin and the amount of sulfuric acid required for the full capacity, and then acid wash the Na-type resin according to the amount of acid added when the molar ratio of the H-type to the Na-type is 1:4 = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0066] (5) The solution S3 is passed into an iminodiacetic acid chelating resin column having a mass ratio of H type to Na type of 1:4, and the flow rate is controlled to be 1 BV / h. Nickel is adsorbed by the resin, and the adsorption rate of nickel reaches 98.9%. The adsorbed solution S4, i.e., a solution containing ferrous sulfate, is obtained. The ferrous sulfate can be obtained by further separation, i.e., evaporation concentration or cooling crystallization.
[0067] (6) A sulfuric acid solution with a mass fraction of 30% was used to desorb the resin. The volume of sulfuric acid was 5BV and the desorption rate was 4BV / h. Then, 2BV of pure water was used for washing. The desorption solution mixed with the sulfuric acid desorption solution was used to measure the nickel content. The nickel desorption rate was 98.4%.
[0068] (7) The nickel sulfate solution obtained in step (6) was evaporated and concentrated at 60° C. for 4 h, and the concentration of nickel sulfate in the concentrated solution was 96 g / L.
[0069] (8) The concentrated liquid was cooled and crystallized at 20°C for 4 hours to obtain nickel sulfate crystals.
[0070] Comparative Example
[0071] The basic steps are the same as those in Example 1, except that no reducing agent is introduced before resin adsorption. The specific steps are as follows:
[0072] (1) Weigh 50g of nickel-iron alloy (main content: Ni: 20.5%; Fe: 64.8%; Cr: 4.2%), mix it with 20% sulfuric acid solution in a pressure autoclave at a solid-liquid ratio of 1:10, react for 7h under the conditions of N2:O2 volume ratio of 9:1 and leaching temperature of 120℃, filter and obtain leachate S1. The leaching rate of nickel in the leachate S1 is 99.2%, the leaching rate of iron is 96.3%, and the leaching rate of chromium is 74.6%. (2) Slowly add iron powder to the leachate S1, and continuously measure the pH of the solution during this period. When the pH of the solution is 3.0, stop adding iron powder, filter it and obtain the chromium-free solution S2.
[0073] (3) Wash the Na-type resin with a 4% acid solution until the pH reaches 3-4 and the resin is washed to neutral; soak 5 mL of the resin in 200 mL of a 1 mol / L sodium hydroxide solution for 2 h, take 20 mL of the soaking solution, add phenolphthalein thereto, and titrate with 1 mol / L sulfuric acid until the red color is basically faded to obtain the H-type resin and the amount of sulfuric acid required for the full capacity, and then acid wash the Na-type resin according to the amount of acid added when the molar ratio of the H-type to the Na-type is 1:2 = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
[0074] (4) The solution S3 is passed into a CH-90 resin column having a mass ratio of H type to Na type of 1:2, and its flow rate is controlled to be 0.5 BV / h. Nickel is adsorbed by the resin, and the adsorption rate of nickel reaches 69.5%. The adsorbed solution S4 is obtained, i.e., a solution containing ferrous sulfate. Ferrous sulfate can be obtained by further separation, i.e., evaporation concentration or cooling crystallization.
[0075] (5) A sulfuric acid solution with a mass fraction of 40% was used to desorb the resin. The volume of sulfuric acid was 3BV and the desorption rate was 2BV / h. Then, 2BV of pure water was used for washing. After mixing with the sulfuric acid desorption solution, the nickel content was measured. The nickel desorption rate was 95.6%.
[0076] (6) The nickel sulfate solution obtained in step (5) was evaporated and concentrated at 80° C. for 6 h, and the concentration of nickel sulfate in the concentrated solution was 90 g / L.
[0077] (7) The concentrated liquid was cooled and crystallized at 10° C. for 4 h to obtain nickel sulfate crystals.
[0078] Combining Example 1 and the comparative example, it can be seen that the adsorption rate of nickel can be effectively improved by adding a reducing agent before resin adsorption. That is, the reducing agent is introduced before resin adsorption, which can effectively promote the stability of the resin adsorption process, reduce the oxidation of the carbon chain or functional group of the resin by many oxidizing substances in the adsorbed liquid to cause carbon chain breakage and functional group changes, and effectively avoid the denaturation of the resin and reduce the adsorption performance.
Claims
1. A method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials, characterized in that: The steps include: (1) immersing the nickel-iron alloy in an acid solution and leaching under pressure at a volume ratio of N2 to O2 of (7-9):(1-3) to obtain a leachate S1; (2) adding a neutralizing agent to the leachate S1 to adjust the pH to 2.5-3, precipitating chromium and performing solid-liquid separation to obtain a solution S2; (3) adding a reducing agent to solution S2 to obtain solution S3; (4) passing the solution S3 through a resin column having an H-type and Na-type molar ratio of 1:(0.5-4) to separate the nickel ions alone and simultaneously obtain a solution S4 containing ferrous sulfate after adsorption, and separating the solution S4 to obtain ferrous sulfate; (5) Desorbing the resin to obtain a nickel sulfate solution, and then evaporating, concentrating, cooling and crystallizing to obtain nickel sulfate crystals.
2. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (1), the leaching temperature is 100-200° C., the leaching time is 5-10 h, and the solid-liquid ratio of the nickel-iron alloy to the acid solution is 1:(1-40) g / L.
3. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (1), the leaching rate of nickel in the leaching solution S1 is 98-100%, the leaching rate of iron is 95-100%, and the leaching rate of chromium is 60-80%.
4. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (2), the neutralizing agent is iron powder or nickel hydroxide.
5. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (3), the reducing agent includes sodium disulfite, sodium sulfite or sodium bisulfite.
6. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (4), the resin column with a molar ratio of H type to Na type of 1:(0.5-4) is obtained by the following steps: determining the amount of sulfuric acid required for the full capacity when the Na type is converted into the H type resin, and then acid washing the Na type resin according to the amount of acid added when the conversion to the H type and Na type molar ratio of 1:(0.5-4) = the amount of sulfuric acid required for the full capacity / the proportion of the hydrogen type.
7. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (4), the adsorption flow rate is 0.4-1BV / h.
8. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (5), the desorbent used for desorption is a 20-40% sulfuric acid solution, the volume of the sulfuric acid solution is 3-5BV, and the desorption rate is 1-4BV / h.
9. The method for preparing battery-grade nickel sulfate and ferrous sulfate respectively using nickel-iron alloy as raw materials according to claim 1, characterized in that: In step (5), the evaporation concentration temperature is 60-100°C, and the cooling crystallization temperature is 0-20°C.
Citation Information
Patent Citations
Method for extracting nickel and cobalt by enclosed leaching nickel oxide mine
CN101418379A
Method for separating and enriching nickel from leach liquor used for pickling and vulcanizing tailing
CN102994753A
Method for recycling inactivated Fe2O3 / Ni2O3 / Al2O3 catalyst
CN111233015A
Method for combined efficient utilization of limonite type laterite-nickel ore and magnesian type laterite-nickel ore
CN115180653A
Method for preparing nickel sulfate from low nickel matte
CN116873990A